γ-Li4-3xAlxGeO4 solid electrolytes: Phase equilibria, conductivity and glass-transition-like behaviour - Lee, Chnoong Kheng; West, Anthony R. (Royal Society of Chemistry (RSC), 1993)
The phase diagram Li4GeO4-LiAlGeO4 has been shown to contain a short range of Li4GeO4 solid solutions, a range of γ solid solutions, Li4-3xAlxGeO4 [where (0.04-0.13) < x < 0.30] and a line phase, α, with x = 0.375. The γ solid solutions are stable up to melting at 1140-1160°C and the α phase is stable between 1080 and 1160°C only. X-Ray powder data are given for α and γ solid solutions. The γ solid solutions exhibit a remarkable temperature-independent conductivity of Li+ ions above ca. 700°C which is particularly noticeable at low values of x. With decreasing temperature, Li+ ion motion is increasingly thermally activated, with an activation energy of 0.45-0.60 eV at temperatures below 300°C. The highest room-temperature conductivity was ca. 2 x 10-5 Ω-1 cm-1 in freshly quenched γ samples of x = 0.10, but the conductivity gradually decreased with time owing to ageing. There is evidence from differential scanning calorimetry (DSC) studies of a sluggish order-disorder transition at 200-250°C involving the Li+ ion site occupancies, which has many of the characteristics of a glass transition. An additional second-order transition occurs at 480-500°C which is attributed to a change from disordered to liquid-like properties of the mobile Li+ ions.